Social Support and Psychological Resilience: Understanding Their Role in Reducing Psychological Distress - Komal Khan; Alishba Rehman; Nimra Farooq, (Dialogue Social Science Review (DSSR), 2025)
Background: Psychological distress is a significant mental health concern, contributing to various negative emotional and physical outcomes. Social support and psychological resilience are both critical factors that have been identified as protective against psychological distress. However, the interaction between these factors in reducing distress remains insufficiently explored. Objectives: This study aims to examine the individual and combined effects of social support and psychological resilience on psychological distress. Specifically, it investigates how social support influences distress in individuals with varying levels of resilience and whether psychological resilience moderates the relationship between social support and distress. Methods: A cross-sectional design was employed with a sample of 300 adults. Participants completed standardized surveys: the Multidimensional Scale of Perceived Social Support (MSPSS), Connor-Davidson Resilience Scale (CD-RISC), and the Kessler Psychological Distress Scale (K10). Pearson’s correlation and multiple regression analyses were used to assess the relationships between social support, resilience, and distress. Moderation analysis was conducted to examine whether resilience moderated the effect of social support on psychological distress. Results: The results revealed significant negative correlations between both social support (r = -0.45, p < 0.001) and psychological resilience (r = -0.63, p < 0.001) with psychological distress. Furthermore, psychological resilience was found to significantly moderate the relationship between social support and distress (β = -0.13, p < 0.05). The buffering effect of social support was stronger for individuals with higher resilience. Conclusions: This study underscores the importance of both social support and psychological resilience in reducing psychological distress. The findings suggest that resilience enhances the benefits of social support, acting as a buffer against distress. Interventions aimed at improving resilience may complement social support efforts, especially for individuals who lack strong social networks. Keywords: Social support, psychological resilience, psychological distress, buffering hypothesis, mental health, moderation analysis, coping, mental well-being, stress management.